2019
DOI: 10.1021/acs.inorgchem.9b03138
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-Substituted Ruthenium(II) Complex: A New Strategy for a G-Quadruplex DNA Fluorescent Probe

Abstract: A new strategy for a G-quadruplex fluorescent probe based on a nitro-substituted ruthenium complex is described. G-quadruplex DNA can be distinguished from double-or single-strand DNA by the naked eye. This ability originates from variation of the degree of protection of the nitro group on the complex from water by G-quadruplex and other structure DNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Previous works have shown that the emission intensity of nitro-substituted ruthenium (II) complex could be affected by the environment change due to solvent polarity. [1,2] For example, complex 2 [Ru (bpy) 2 (hnoip)] 2+ emits weak luminescence in water, but displays strong luminescence in organic solvent or after binding doublestrand DNA. Liu et al explained that the special phenomenon is caused by the hydrophobic environment provided by organic solvents and DNA.…”
Section: Fluorescence Spectra Of Complex 1 In Various Solventsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous works have shown that the emission intensity of nitro-substituted ruthenium (II) complex could be affected by the environment change due to solvent polarity. [1,2] For example, complex 2 [Ru (bpy) 2 (hnoip)] 2+ emits weak luminescence in water, but displays strong luminescence in organic solvent or after binding doublestrand DNA. Liu et al explained that the special phenomenon is caused by the hydrophobic environment provided by organic solvents and DNA.…”
Section: Fluorescence Spectra Of Complex 1 In Various Solventsmentioning
confidence: 99%
“…Previous work shows that the nitro group on ruthenium (II) complexes presents two kinds of functions on its emission properties. [1][2][3][4] One is to reduce the emission intensity of ruthenium (II) complex due to the strong electro-withdrawing ability of the nitro group. The other is to make the fluorescence of ruthenium (II) complex be sensitive to the environment change, which usually leads to strong fluorescence in organic solvent and weak fluorescence in water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luminescent transition metal complexes, especially ruthenium (II) (Ru(II)) and iridium (III) (Ir(III)) complexes, have received considerable attention in the development of bioassay and imaging probes [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%